An overview on measurements of natural radioactivity in Malaysia - Ahmad, Nisar; Jaafar, Mohamad Suhaimi; Bakhash, Muhammad; Rahim, Muhammad (Elsevier, 2015)
Humans are always exposed during their lives to ionizing radiation arising outside and within the earth. The exposure to these radiation occurs from natural sources such as radioactive elements in rocks and soil, internal exposure form radioactive elements through water, food and air and cosmic rays entering from outer space to earth's atmosphere. About 87% of the radiation dose received by human beings is due to natural radiation, it is essential to assess the radiation doses in order to control possible health effects from such natural sources. In this regard, a number of articles have been appeared for Malaysia in international research journals, which have been reviewed and complied in this article. Most of these articles are about the measurement of activity concentrations of primordial (238U, 232Th, 226Ra and 40K) and anthropogenic (137Cs) radionuclide's and gamma dose rate in environmental samples using HPGe and NaI (Tl) survey meter.